Isolation, Identification, and Antimicrobial Susceptibility of Escherichia coli in Contaminated Milk and Milk Products - Nsaif, Ayat Abd-Aljaleel (Medical Science Journal for Advance Research, 2025)
Milk is regarded as a full and healthy sustenance for newborn mammals and humans; nonetheless, it serves as an effective medium for many bacteria. Milk consumption in raw form and its derivatives is prevalent, resulting in the spread of different illnesses. The research aimed to extract and identify Escherichia coli from raw milk and dairy products derived from cattle in selected dairy farms in Diyala. A total of 30 samples: 10 of raw milk, 10 of cheese, and 10 of kemeer was collected from cattle in selected dairy farms in Diyala. Culture media were prepared according to the manufacturer’s instructions. Also, antimicrobial susceptibility test was done to isolated strains. The result showed that all samples were contaminated with E. coli according to the following percentage respectively (Milk 70%, Chesses 40%, Kemer 60%). The antimicrobial susceptibility test findings were generated from the isolated strains, with all isolates evaluated against a panel of 12 antimicrobials. E. coli was resistance to FOX, AMP, TM while it was sensitive to others.